TRS and ORP Comparison Report - Faculty Senate, Valdosta State University (Valdosta State University Archives and Special Collections, 2016)
Valdosta State University. Faculty Senate, TRS and ORP Comparison, January 28, 2016. Teacher retirement of Georgia and Option Retirement Plan document.
1 electronic document. faculty-senate_20160128_retirement.pdf. 60 pages. 11638694 bytes.
Keywords: Faculty Senate (Valdosta State University); Electronic records; Corporation reports; Teachers--Retirement